2011
DOI: 10.4238/vol10-1gmr990
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic behavior in nonaploid accessions of Brachiaria humidicola (Poaceae) and implications for breeding

Abstract: ABSTRACT. Brachiaria humidicola is a grass adapted to seasonally swampy grasslands in Africa; two cultivars, 'common' and Llanero, are widely used in Brazilian pastures. New cultivars are in great demand in order to diversify current production systems to achieve improved quality and yield. Cytological analyses of 55 accessions of this species available from the Embrapa Beef Cattle germplasm collection revealed that 27 are apomictic and have 2n = 54 chromosomes. Chromosome pairing as bi-to nonavalent associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Therefore, the results support the parents H031 and BRS Tupi, which are hexaploid and have 36 chromosomes (2n=6x=36), are genetically distant from cv. Comum, which has 54 chromosomes (2n=9x=54) (Boldrini et al 2011). In this way, the group formed by the hybrids was subjected again to analyses of genetic divergence and clustering (second cycle), for the formation of subgroups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results support the parents H031 and BRS Tupi, which are hexaploid and have 36 chromosomes (2n=6x=36), are genetically distant from cv. Comum, which has 54 chromosomes (2n=9x=54) (Boldrini et al 2011). In this way, the group formed by the hybrids was subjected again to analyses of genetic divergence and clustering (second cycle), for the formation of subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the intraspecific hybridization in B. humidicola can only be made between hexaploid accessions 2,8,4,5,14,9,12,13,7,12 DMY II 3,11 III 6 IV 1 V 10 I 9,13,14,4,5,2,8,7,12 NSBR II 3,11 III 1 e 6 IV 10 I 2,8,5,4,9,14,13,12 with 36 chromosomes, considering that there is only one sexual accession identified with this ploidy and chromosome number. This restriction excludes the possibility of crosses with the apomictic commercial cultivars Comum and Llanero, which are nonaploid with 54 chromosomes (Boldrini et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Cytogenetic characterization studies with this Urochloa collection started in 1998 at State University of Maringa. Cytogenetic analyses, such as the evaluation of chromosomal behavior in all phases of meiosis and counting the number of chromosomes, have already been performed with accessions of U. brizantha ( Mendes-Bonato et al, 2002a ; Risso-Pascotto et al, 2003a ; Pagliarini et al, 2012 ), U. decumbens ( Risso-Pascotto et al, 2002 ; Mendes-Bonato et al, 2002b ; Junqueira-Filho et al, 2003 ; Ricci et al, 2010 , 2011 ), U. ruziziensis ( Risso-Pascotto et al, 2003b , 2005 ), and U. humidicola ( Boldrini et al, 2006 ; Adamowski et al, 2007 ; Boldrini et al, 2011a , b ), among other species. Cytogenetic analyses have also been performed with interspecific hybrids ( Risso-Pascotto et al, 2004a , b ; Mendes-Bonato et al, 2006 , 2007 ; Adamowski et al, 2008 ; Felismino et al, 2010 , 2012 ; Fuzinatto et al, 2012 , 2017 ; da Rocha et al, 2019 ; de Campos Moraes et al, 2019 ) as well as intraspecific hybrids of U. decumbens ( Souza, 2013 ).…”
Section: Germplasm Resourcesmentioning
confidence: 99%
“…Chromosome research, particularly meiotic analysis, has been performed with Urochloa species and hybrids ( Mendes-Bonato et al, 2002a , b , 2006 , 2007 ; Risso-Pascotto et al, 2002 , 2003a , b , 2004a , b , 2005; Junqueira-Filho et al, 2003 ; Boldrini et al, 2006 , 2009 , 2011a , b ; Adamowski et al, 2007 , 2008 ; Felismino et al, 2010 , 2012 ; Ricci et al, 2010 , 2011 ; Fuzinatto et al, 2012 , 2017 ; Pagliarini et al, 2012 ; Souza, 2013 ). These studies have revealed several abnormalities typical of allopolyploids and segmental allopolyploids, such as asynchronous chromosome segregation, intragenomic pairing, and the presence of multivalents and micronuclei.…”
Section: Genomic Tools and Resourcesmentioning
confidence: 99%
“…Algumas espécies do gênero Brachiaria, como B. brizantha Segundo Pagliarini et al (2007), no gênero Urochloa, a maioria das espécies é poliploide, principalmente tetraploide e apomítica. Os números básicos de cromossomos relatados para o gênero correspondem a x = 6, x = 7 e x = 9 Boldrini et al, 2011;Risso-Pascotto et al, 2003, 2006a, 2009.…”
Section: Agropecuária No Brasilunclassified